2013
DOI: 10.1590/s0103-84782013000500015
|View full text |Cite
|
Sign up to set email alerts
|

Metodologias de controle de qualidade de análises granulométricas do solo

Abstract: RESUMO A qualidade da análise granulométrica é imprescindível para a adequada classifi cação textural dos solos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…The methods recommended for routine laboratory analysis produce errors (Ruiz, 2005). In view of the diversity of forms and methods adopted by many soil laboratories for particle size determination, Klein et al (2013) evaluated two methods for quality control of particle size analyses and found that size fractions with the highest percentage of misclassification are silt and clay. Furthermore, clay is the fraction that causes inconsistencies in the results due to its difficulty of particle dispersion (Suzuki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The methods recommended for routine laboratory analysis produce errors (Ruiz, 2005). In view of the diversity of forms and methods adopted by many soil laboratories for particle size determination, Klein et al (2013) evaluated two methods for quality control of particle size analyses and found that size fractions with the highest percentage of misclassification are silt and clay. Furthermore, clay is the fraction that causes inconsistencies in the results due to its difficulty of particle dispersion (Suzuki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A análise granulométrica é fundamental para caracterização do solo e indispensável para a adoção de práticas adequadas ao seu manejo. Isso porque a granulometria, ou distribuição do tamanho das partículas do solo, interfere diretamente na susceptibilidade à compactação, na disponibilidade hídrica, na capacidade de troca de cátions (Klein et al, 2013) e na aeração, que, por sua vez, pode interferir na absorção de nutrientes pelas plantas.…”
Section: Introductionunclassified
“…A fração argila tem grande influência sobre as propriedades do solo devido a sua grande área superficial específica e densidade de carga elevada, o que confere a essa fração alta reatividade química (Jury & Horton, 2004). Com essa preocupação, pesquisas têm sido realizadas nas regiões sul (Klein et al, 2013), sudeste (Mauri et al, 2011) e nordeste (Cunha et al, 2014) do Brasil. Na região Norte, ainda há carência de trabalhos que avaliem a eficiência dos métodos de análise granulométrica nos solos da região.…”
Section: Introductionunclassified
“…As amostras de solo com estrutura alterada foram utilizadas para a determinação da umidade gravimétrica nas tensões de 500, 1000 e 1500 kPa, em um psicrômetro (WP4 Dewpoint Potentia Meter) (GUBIANI et al, 2013;KLEIN et al, 2013). A umidade volumétrica foi obtida do produto entre a umidade gravimétrica e a densidade do solo correspondente à camada amostrada.…”
Section: Posição No Terreno E Amostragens De Solounclassified